14 The use of sacubitril/valsartan: a real world experience in a high volume specialist heart failure service. (5th October 2017) - Murray, G; Barrett, M; Earls, S; Hammond, M; Campbell, P; O'Hanlon, R; McDonald, K
Abstract : Introduction: Sacubitril/Valsartan is a novel therapy in the treatment of heart failure with reduced ejection fraction, demonstrating a lower cardiovascular mortality and heart failure hospitalisation rates compared to standard therapy. We analysed the additive value of sacubitril/valsartan therapy on a well-managed real world heart failure cohort. Specifically, we aimed to see if there was an appreciable reduction in markers of fibrosis and cardiovascular risk – N-terminal pro-B-type natriuretic peptide (NT pro-BNP) and ST2, a soluble interleukin-2 receptor. We also qualitatively assessed change in diuretic therapy and subjective symptoms of wellness. Methods: All patients commencing sacubitril/valsartan therapy over an 18-month period were included. Of note, patients had been stable on angiotensin axis blockade prior to commencement. Patients were commenced on sacubitril/valsartan at the lowest dose and titrated upwards to either the maximum dose or to maximum tolerated dose based on renal function, blood pressure and symptoms. Serum renal function, NT pro-BNP and ST2 were measured at baseline and after completion of titration of therapy. Differences in baseline and follow-up biomarkers were analysed using a paired student's t -test. A p value of 0.05 or less indicated a significant change with therapy. Results: 131 patients were included during the observed time period. A total of 19 patients (14.5%) discontinued therapy due to intolerable side effects. Primary reasons for discontinuation of therapy included hypotension (n=10), gastrointestinal disturbances (n=4), hyperkalaemia (n=1) and others (n=4). Figure 1 demonstrates the main reasons for discontinuation of sacubitril/valsartan as a result of adverse side effects.A total of 19 patients discontinued sacubitril/valsartan. Of patients tolerating therapy, 49 (43.8%) had a reduction in diuretic dose as compared to 3 (2.7%) requiring an increase. 49 patients (43.8%) self-reported a subjective improvement in heart failure symptoms as compared to 4 (3.6%) who reported deterioration in symptoms. Change in biomarkers in patients completing therapy were assessed by measuring pre and post treatment serum levels. Table 1 below demonstrates the affects sacubitril/valsartan therapy had on the analysed biomarkers. Conclusion: These data demonstrate the efficacy of sacubitril/valsartan in improving symptoms and biomarkers of cardiovascular risk whilst reducing the need for diuretic therapy in a real-world population. Reaassuringly, a strong signal was seen for reduction in NT pro-BNP. Intolerance to the novel therapy was low, although further experience with use of the agent may help avoid discontinuations in the future, especially where physicians may not consider reduction in diuretic dose during therapy to minimise side-effects